Communication Model of Indonesian Student Organizations in China through the Indonesian Movement Helps - Dani Fadillah; Uspal Jandevi (Jurnal Ilmu Komunikasi, 2020)
The Indonesian Movement Helps organization located in China helps Indonesian students while studying in China, but some Indonesian students initially had difficulty communicating with the organization. Many Indonesian students are victims of irresponsible scholarship agents. This research aims to analyze the communication barriers of the Indonesian Movement Helps organization in helping Indonesian students in China. This research method is qualitatively descriptive with data collection techniques through observation and in-depth interviews. Data analysis techniques using SWOT analysis. The results found a communication model of Indonesian student organizations in China through the internalization of the climate and culture of the word of mouth communication in Indonesian Movement Helps. The substance of this research is the communication model of Indonesian student organizations in China through the internalization of climate and culture of the word of mouth communication that can be applied to student organizations in other countries.